Effect of Mediterranean Diet in Diabetes Control and Cardiovascular Risk Modification: A Systematic Review - Sleiman, Dana; Al-Badri, Marwa R.; Azar, Sami T. (Frontiers in Public Health, 2015)
Background: Over the past few years, there has been a worldwide significant increase in the incidence of type II diabetes (T2DM) with both increase in morbidity and mortality. Controlling diabetes through life style modifications, including diet and exercise has always been the cornerstone in diabetes management. As a matter of fact, a number of studies addressed the potential protective role of Mediterranean diet in diabetic patients. Increasing evidence suggests that the Mediterranean diet could be of benefit in diseases associated with chronic inflammation, including metabolic syndrome, diabetes, obesity as well as atherosclerosis, cancer, pulmonary diseases, and cognition disorders. Methods: A systematic review was conducted on the effect of Mediterranean diet in diabetes control and cardiovascular risk modification as well as the possible mechanism through which this diet might exhibit its beneficial role. We did a comprehensive search of multiple electronic databases such as Medline, Google Scholars, PubMed, and the Cochrane central register data until May 2014. We included cross-sectional, prospective and controlled clinical trials that looked at the associations between Mediterranean diet and indices of diabetes control such HbA1c, fasting glucose, and HOMA, in addition to cardiovascular and peripheral vascular outcomes. Outcome/Conclusion: Most of the studies showed favorable effects of Mediterranean diet on glycemic control and CVD, although a certain degree of controversy remains regarding some issues, such as obesity. Important methodological differences and limitations in the studies make it difficult to compare results, thus further longer term studies are needed to evaluate the long-term efficacy of the Mediterranean diet along with the possibility of explaining its mechanism.